GENERAL ELECTIONS IN A MULTIPATIC SYSTEM AND ITS EFFECT ON NATIONAL POLITICAL STABILITY IN HISTORICAL VIEW - Imawan Sugiharto (GoAcademica Research dan Publishing, 2019)
The multiparty system has a major impact on government and society's stability at large, both directly and indirectly. This system has been implemented since 1950, despite experiencing problems and changes in it. In the reform era, Indonesia reused this system based on democratic principles. The method used is normative juridical with a descriptive analysis approach in the perspective of comparative historical politics. The discussion in this study uses a comparative political approach. From this study, it is known that there is a relationship between the multiparty electoral system, the executive-legislative relationship, as well as the broad impact on national political stability in various fields.